Developing Acid‐Responsive Glyco‐Nanoplatform Based Vaccines for Enhanced Cytotoxic T‐lymphocyte Responses Against Cancer and SARS‐CoV‐2. (17th July 2021) - Gao, Yanan; Zhao, Qingyu; Dong, Huiling; Xiao, Min; Huang, Xuefei; Wu, Xuanjun
Abstract: Cytotoxic T‐lymphocytes (CTLs) are central for eliciting protective immunity against malignancies and infectious diseases. Here, for the first time, partially oxidized acetalated dextran nanoparticles (Ox‐AcDEX NPs) with an average diameter of 100 nm are fabricated as a general platform for vaccine delivery. To develop effective anticancer vaccines, Ox‐AcDEX NPs are conjugated with a representative CTL peptide epitope (CTLp) from human mucin‐1 (MUC1) with the sequence of TSAPDTRPAP (referred to as Mp1) and an immune‐enhancing adjuvant R837 (referred to as R) via imine bond formation affording AcDEX‐(imine)‐Mp1‐R NPs. Administration of AcDEX‐(imine)‐Mp1‐R NPs results in robust and long‐lasting anti‐MUC1 CTL immune responses, which provides mice with superior protection from the tumor. To verify its universality, this nanoplatform is also exploited to deliver epitopes from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) to prevent coronavirus disease 2019 (COVID‐19). By conjugating Ox‐AcDEX NPs with the potential CTL epitope of SARS‐CoV‐2 (referred to as Sp) and R837, AcDEX‐(imine)‐Sp‐R NPs are fabricated for anti‐SARS‐CoV‐2 vaccine candidates. Several epitopes potentially contributing to the induction of potent and protective anti‐SARS‐CoV‐2 CTL responses are examined and discussed. Collectively, these findings shed light on the universal use of Ox‐AcDEX NPs to deliver both tumor‐associated and virus‐associated epitopes. Abstract : Versatile AcDEX‐(imine)‐CTLp‐R nanoparticles are developed by the conjugation of cytotoxic T‐lymphocyte (CTL) peptide (CTLp) and immune‐potentiating adjuvant R837 (R) with partially oxidized acetalated dextran nanoparticles for enhanced CTL responses against tumor cells and severe acute respiratory syndrome coronavirus 2 infected cells.